2006
DOI: 10.1038/sj.onc.1210111
|View full text |Cite
|
Sign up to set email alerts
|

Role of 2-5A-dependent RNase-L in senescence and longevity

Abstract: Senescence is a permanent growth arrest that restricts the lifespan of primary cells in culture, and represents an in vitro model for aging. Senescence functions as a tumor suppressor mechanism that can be induced independent of replicative crisis by diverse stress stimuli. RNase-L mediates antiproliferative activities and functions as a tumor suppressor in prostate cancer, therefore, we examined a role for RNase-L in cellular senescence and aging. Ectopic expression of RNase-L induced a senescent morphology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…A number of IFN response genes have been linked to growth inhibition, senescence and apoptosis [49][50][51][52]. Our results suggest that under normal conditions, IFN-related genes are mostly repressed by the BRCA2 complex, and this repression is released in BRCA2 knockout cells.…”
Section: Discussionmentioning
confidence: 48%
“…A number of IFN response genes have been linked to growth inhibition, senescence and apoptosis [49][50][51][52]. Our results suggest that under normal conditions, IFN-related genes are mostly repressed by the BRCA2 complex, and this repression is released in BRCA2 knockout cells.…”
Section: Discussionmentioning
confidence: 48%
“…The TD and Rnasel −/− mice are currently in widespread many different labs investigating antiviral innate immunity. In addition, Bret Hassel's group reported with us that the Rnasel −/− mice have extended lifespans and that RNase L has a role in cell senescence [77]. Therefore, the Rnasel −/− mice may be useful in aging research.…”
Section: Involvement Of Rnase L In the Antiviral Action Of Ifnsmentioning
confidence: 99%
“…A global comparison of transcripts and proteins bound to both RNase L and TTP will provide a more complete picture of the factors that mediate RNase L substrate targeting in the context of mitogen stimulation. RNase L mediates diverse antiproliferative activities, including quiescence (11), senescence (24), and apoptosis (25,26). Our results demonstrated that RNase L down-regulates mitogen-induced gene expression via transcriptional and post-transcriptional mechanisms suggesting that it plays a functional role to attenuate the proliferative response.…”
Section: Discussionmentioning
confidence: 71%
“…6). Both RNase L and TTP mediate antiproliferative and tumor suppressor activities (6,7,20,(23)(24)(25)(26)64); accordingly, genetic disruption or inactivating mutations in either protein lead to a transformed phenotype in vitro and tumorigenesis in vivo (27,28,101). Furthermore, mutations in RNase L and TTP are correlated with poor prognosis in several human cancers (6, 29 -32, 102).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation